Prenatal Stress Increases the Risk of the FPR2-related Dysfunction in the Brain's Resolution of Inflammation: A Study on the Humanized APPNL-F/NL-F Mouse Model of Alzheimer's Disease - Trojan, Ewa; Frydrych, Jakub; Lasoń, Władysław; Basta-Kaim, Agnieszka (Current Neuropharmacology, 2025)
IntroductionBrain aging is a complex process involving genetic, neurodevelopmental, and environmental factors. Inherent features of this process are cellular senescence, the development of senescence-associated secretory phenotype (SASP), and prolonged inflammation.MethodsRecently, progress has been made in understanding the biological roles of FPR2 receptors and their ligands in the mechanism of inflammation resolution (RoI) in the brain. However, the number of studies comparing the influence of prenatal stress (PS) on RoI in physiological aging and neurodegenerative disorders pathology is very limited, and the data need to be more consistent. Here, we examined whether PS can condition the pattern of age-dependent cognitive and RoI changes in the prefrontal cortex and hippocampus in wild-type and hAPPNL-F/NL-F KI male mice.ResultsWe discovered that in aging, the memory deficits are accompanied by the limitation of the availability of pro-resolving FPR2 ligands, the rising proinflammatory microglia polarization, and inflammatory ligands mediated FPR2 overactivation. Moreover, the present study suggested the subtle role of the RoI deficits in creating brain cells' senescence and shifting the immunomodulators to the proinflammatory direction. PS has been revealed as a substantial factor modulating the profile of inflame-aging in a manner strongly determined by the age of animals and the brain structure under study, mainly in hAPPNL-F/NL-F KI male mice.ConclusionOur results identify the FPR2 receptors as a driver regulating the RoI process in the brain and highlight that PS has diversified the picture of age-dependent neurodegenerative pathology.
Keywords: cellular senescence